An advanced self-care delivery model for leg ulcer management: a service evaluation. (2nd September 2021) - Hallas-Hoyes, Laura; Williamson, Stephanie; Kerr, Andrew; Andrews, Trevor; Calladine, Leanne
Abstract : Background: Lower limb ulceration is a common cause of suffering in patients and its management poses a significant burden on the NHS, with venous leg ulcers (VLUs) being the most common hard-to-heal wound in the UK. It is estimated that over one million patients in the UK have lower limb ulceration, of which 560, 000 were categorised as VLUs, with a cost burden of over £3 billion each year. Objective: The aim of this service evaluation was to assess the effects of implementing a self-care delivery model on clinical outcomes with the intention of limiting face-to-face health professional contact to one appointment every 6 weeks. Method: A suitability assessment was conducted and a cohort of patients were moved to a self-care delivery model. Patient data were collected, anonymised and independently analysed, comparing time to healing against data on file from a previous report. Results: This highlighted that, in 84 of the 95 patients selected, the VLUs had healed by week 24 on the pathway, a further 10 patients' VLUs had healed by week 42 and only one remaining patient reached 42 weeks without healing. Conclusion: These results support the hypothesis that patients with VLUs can self-care and deliver clinical effectiveness. It is recommended that all services explore the possibility of introducing a self-care model for VLU care.